Gough Island (Polar Record, 1940)
According to a note by Allan Crawford ( Geographical Journal , xciv, p. 412) H.M.S. Milford called at Gough Island in the Southern Ocean at the end of March 1938. Following instructions from the Colonial Office, the captain landed with a party to hoist the Union Jack and declare this island a dependency of St Helena. Discovered in the sixteenth century by the Portuguese, and named by them Diego Alvarez, it seems to have been lost sight of until, in 1731, Captain Gough, homeward bound in his ship Richmond round the Cape of Good Hope, sighted an island in the South Atlantic, which henceforth went by his name. It was only slowly that geographers came to the conclusion that Diego Alvarez and Gough were one and the same island, and then the former name gradually disappeared from charts. Gough Island has been claimed as British territory since Captain Gough reported it.